2016
DOI: 10.1016/j.freeradbiomed.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1-derived bilirubin counteracts HIV protease inhibitor-mediated endothelial cell dysfunction

Abstract: The use of HIV protease inhibitors (PIs) has extended the duration and quality of life for HIV-positive individuals. However there is increasing concern that this antiviral therapy may promote premature cardiovascular disease by impairing endothelial cell (EC) function. In the present study, we investigated the effect of HIV PIs on EC function and determined if the enzyme heme oxygenase (HO-1) influences the biological action of these drugs. We found that three distinct PIs, including ritonavir, atazanavir, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…17 To potentially explain these mixed findings, atazanavir and other protease inhibitors have been shown to actually increase endothelial dysfunction, oxidative stress, and von Willebrand factor, thereby counteracting some of the benefits of the elevated bilirubin levels. [46][47][48] Because CVD rates did not differ by atazanavir status in the VACS analysis, it is unlikely that the bilirubin effect is merely a surrogate for a protective effect afforded by atazanavir use. If replicated successfully, these results have potential clinical implications not only for CVD risk assessment and reduction but also in other chronic conditions, including cancers, demyelinating neuropathies, seasonal affective disorder, 14 and rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…17 To potentially explain these mixed findings, atazanavir and other protease inhibitors have been shown to actually increase endothelial dysfunction, oxidative stress, and von Willebrand factor, thereby counteracting some of the benefits of the elevated bilirubin levels. [46][47][48] Because CVD rates did not differ by atazanavir status in the VACS analysis, it is unlikely that the bilirubin effect is merely a surrogate for a protective effect afforded by atazanavir use. If replicated successfully, these results have potential clinical implications not only for CVD risk assessment and reduction but also in other chronic conditions, including cancers, demyelinating neuropathies, seasonal affective disorder, 14 and rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 97%
“…In one of these trials, endothelial function improved,16 whereas the second study showed only a reduction in low‐density lipoprotein levels and blood pressure 17. To potentially explain these mixed findings, atazanavir and other protease inhibitors have been shown to actually increase endothelial dysfunction, oxidative stress, and von Willebrand factor, thereby counteracting some of the benefits of the elevated bilirubin levels 46, 47, 48. Because CVD rates did not differ by atazanavir status in the VACS analysis, it is unlikely that the bilirubin effect is merely a surrogate for a protective effect afforded by atazanavir use.…”
Section: Discussionmentioning
confidence: 99%
“…52 Finally, bilirubin derived from HO-1 has been reported to inhibit the protease activity of HIV, which negatively affects virus replication. 53 The beneficial properties of HO-1 expression have also been reported for viruses that produce lung disease, such as influenza virus infection. Mice that overexpress HO-1 in the lungs display less inflammatory cell infiltration into the lungs and decreased apoptosis of respiratory epithelial cells, as compared to control mice, suggesting that HO-1 expression prevents an exacerbated immune response in this tissue and subsequent damage.…”
Section: Antiviral Activity Mediated By Ho-1 Inductionmentioning
confidence: 93%
“…For example, as a downstream metabolite of HO-1, BV has been demonstrated to act as a key effector against HCV replication by activating the antiviral IFN response and inhibiting the NS3/4A protease activity of HCV (Lehmann et al, 2010;Zhu et al, 2010). HO-1 derived from BR has been reported to suppress human herpes simplex type 1 virus (HSV-1) and EV71 infection, as well as protease activity of DENV and HIV (Santangelo et al, 2012;Olagnier et al, 2014;Liu et al, 2016). Iron ions derived from HO-1 have been demonstrated to participate in key cellular processes that are dependent on this metal, either promoting or suppressing the translation of particular mRNAs, depending on its concentrations (Eisenstein et al, 1991).…”
Section: Introductionmentioning
confidence: 99%